Kelam İlminin "Kelam" olarak İsimlendirilmesinde Vâsıl b. Ata'nın Takip Ettiği Yöntemin Muhtemel Katkıları Üzerine - Taşçi, Özcan (Dinî araştırmalar, 2006)
It is known that the word "kalam" means speech on the various objects of Islamic Theology according to the Qur’an and the reason. This is very important principle of Islamic Theology. That principle as a method of Kalam/Theology is old and well known by the Mu’tazilite Theologians, first of whom was probably Wasd b. Ata, who was known as establisher of this theology-school. In this article is emphasized the practice of this method by Wasil and its influence on Kalam in history